Numbered Musical Notation Composer - Benny Pinontoan; Audy Kenap; Debby Paseru; Inggrid Alista Paendong (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
Computer and it’s technology has been given so many advantages in any side, also in music. Computer’stechnology allows people to build application to compose music in any musical notation. Besides, computer’stechnology in music also allows to edit and save the composed notation easily, compare to use paper andhandwriting (manually). Some applications of musical notation have been built but generally they were built instandard notation system and it causes the use of the applications are limited to people who know well aboutstandard musical notation. The goal of this thesis is to build the application of musical notation in numberedsystem that can be used by anyone, also provides the simply of editing and safely storage. Numbered MusicalNotation Composer (NMNC) is an application to compose musical notation in numbered system. It is developedbased on algorithm and using Borland Delphi 6.0. By the use of this application user can not only composemusic in numbered notation easily, but also listen the sound, and do not need so much time in editing.Keywords: Computer’s technology in music, standard musical notation, numbered musical notation.